Voluntary Counseling and Testing (VCT) services and its role in HIV/AIDS prevention and management in Nepal (South East Asia Journal of Public Health, 2014)
HIV/AIDS has emerged as a serious epidemic in Nepal, concentrated amongst the most-at-risk populations. Volun-tary Counseling and Testing (VCT) is a proven strategy for the prevention and management of HIV/AIDS especially in developing countries. Given that the utilization of VCT is low in Nepal, it is important to understand the barriers and challenges that Nepal is facing in the provision and utilization of these services. This study aimed to provide recommendations for policy makers to improve the utilization of VCT services in Nepal. A qualitative study of VCT health service providers and government officials was undertaken in 4 cities of Nepal. Sixteen interviews, three joint interviews and one focus group discussion were conducted, audio recorded and transcribed verbatim. Data were then analyzed using a thematic analysis framework and major themes were identified. Various barriers including socio-cultural issues, geography, the presence of stigma and discrimination faced by people with HIV/AIDS and a lack of knowledge and awareness were identified as important factors limiting the utilization of VCT services. Current gov-ernment efforts to improve VCT service provision, although promising, require ongoing development. Systemic barriers included the sustainability of the temporary NGO VCT services, lack of staff and training, inadequate moni-toring and evaluation and limited access to services for people living in rural areas. To increase the sustainability and utilization of VCT services, the Government can intervene in a number of areas including the integration of VCT services with existing primary health care services and addressing ongoing education and quality assurance. South East Asia Journal of Public Health 2013; 3(1): 10-16 DOI: http://dx.doi.org/10.3329/seajph.v3i1.17705